The Potential Utility of the Patient Health Questionnaire as a Screener for Psychiatric Comorbidity in a Chronic Disabling Occupational Musculoskeletal Disorder Population. Issue 2 (7th January 2015) - Asih, Sali; Mayer, Tom G.; Bradford, E. McKenna; Neblett, Randy; Williams, Mark J.; Hartzell, Meredith M.; Gatchel, Robert J.
Abstract: Objectives: The patient health questionnaire (PHQ) is designed for screening psychopathology in primary care settings. However, little is known about its clinical utility in other chronic pain populations, which usually have high psychiatric comorbidities. Design: A consecutive cohort of 546 patients with chronic disabling occupational musculoskeletal disorder (CDOMD) was administered and compared upon psychosocial assessments, including the PHQ and a structured clinical interview for DSM‐IV (SCID). Four PHQ modules were assessed: major depressive disorder (MDD), generalized anxiety disorder (GAD), panic disorder (PD), and alcohol use disorders (AUD) [including both alcohol abuse and dependence]. Based on the SCID diagnosis, sensitivity and specificity were determined. Results: The specificity of the PHQ ranged from moderate to high for all 4 PHQ modules (MDD, 0.79; GAD, 0.67; PD, 0.89; AUD, 0.97). However, the sensitivity was relatively low: MDD (0.58); GAD (0.61); PD (0.49); and AUD (0.24). The PHQ was also associated with psychosocial variables. Patients whose PHQ showed MDD, GAD, or PD reported significantly more depressive symptoms and perceived disability than patients who did not ( Ps  < 0.001). Patients with MDD or GAD reported significantly higher pain than those without ( Ps  < 0.001). Conclusions: The strong specificity of the PHQ appears to be its primary strength for this cohort. Due to its high specificity, the PHQ could be employed as an additional screening tool to help rule out potential psychiatric comorbidity in patients with CDOMD. The low sensitivity of the PHQ in this population, however, remains a weakness of the PHQ.